P1_3_Feasibility Study for Heating an Underwater Construct with the use of a Heat Pump. - Feeley, Mathew; Benson, Lucy; Nguyen, Minh Hai (Physics Special Topics, 2009)
The possibility for heating an underwater dome using a heat pump is investigated. It was found that a heat pump would over seven times more efficient than any other electric heaters.